High-Penetration, without Storage, PV Solar-Diesel Generator In Isolated System - Mazin Mustafa, Mahdi; Abu Zaharin, Ahmad; Ekhlas, Mhawi (2015)
The aim of this paper is to reduce the cost of supplying electricity in remote area and to get optimal operation of the distribution network including renewable energy sources. In actual power system operations, the load is changing continuously and randomly, as the ability of the generation to track the changing load is limited due to physical/technical considerations, to maintain the desired active output power of a generator matching with the changing load, there results an imbalance between the actual and the scheduled generation quantities. In recent years, many facilities all over the world the move towards renewable energy uses. For example, wind or photovoltaic power (PV) is an alternative, a source of clean energy and sustainable electricity production. PV certainly does not need to be tall and strong tower, as well as lacking of any vibration or noise, and does not need to be refrigerated. On the other hand volatility and rising fuel prices with considerations of greenhouse gas emission, and carbon footprint reduction therefore, certain features make PV generation worthwhile to consider in planning and electricity network operations now and in the future. The simulation system model and tested using MATLAB/ Simulink and the results are presented.